Product-Market Profile Research in Dairy Products Sector - Radev, Radko (Research Papers, 2014)
Current paper reviews the issues related to the product-market profile of the manufacturers of dairy products in Bulgaria. The author’s interest in this subject is caused by his participation in elaboration of business strategy for one of the leading manufacturers in the dairy products sector. During the process of strategy elaboration a comprehensive study was carried out, which comprises all major competitors in the sector.The key role of product-market profile was outlined during the study. On one hand, its exploration gives the opportunity to determine the product specialization in the sector, as well as the applied product-market and competitive strategies. On other hand, the place of product-market profile for making related decisions is highlighted. From a methodological point of view, the paper presents the main product and market characteristics that determine the product-market profile of the companies. A modified version of the Boston consulting group matrix is presented for the complex assessment of product-market profile. Its outputs are at the core of the proposed product and market characteristics.
Keywords: Product-market profile; Business strategies; Competitive analysis; Product policy